AB0495 INCREASED WORK LOSS DURING PREGNANCY IN WOMEN WITH SYSTEMIC LUPUS ERYTHEMATOSUS COMPARED TO MATCHED HEALTHY CONTROLS. (June 2019) - Blomjous, Birgit; Wee, Marieke Ter; Voskuyl, Alexandre; Vries, Hanneke de; Bultink, Irene E.M.
Abstract : Background: Women with systemic lupus erythematosus (SLE) might be more vulnerable to reduce or stop working during pregnancy because of the increased risk of pregnancy complications compared to the general population. However, no data on work loss during pregnancy and return to work after maternity leave in patients with SLE are available. Objectives: We aimed to investigate several work outcomes during and after pregnancy in women with SLE compared to matched pregnant controls. Methods: A case-control study on employment was performed in pregnant women with SLE and matched controls. Matching criteria were age, year of delivery, and number of living infants. Employment was defined as having ≥8 hours/week of paid work before conception. Four work outcomes were investigated: interruption of work for >1 week during pregnancy, complete cessation of work for >1 week until delivery, reduction in working hours during pregnancy, and the time in weeks to return to work after maternity leave. Results: A total of 42 women were included (21 SLE patients, 21 controls). Mean SELENA-SLEDAI before pregnancy in SLE patients was 2.6 (SD 2.3). Interruption of work for >1 week or completely stop working during pregnancy occurred in 10 SLE women, compared to 2 controls (OR=8.6, 95% CI [1.6-46.8], p=0.012). From the women who completely stopped working until delivery (n=8), 7 women had SLE (OR=1.4, 95% CI [0.07-28.1], p=0.826). In addition, in women continuing work, reduction of working hours occurred in 5 women with SLE versus 3 controls (OR=1.9, 95% CI [0.4-9.1], p=0.436). After delivery, the median (IQR) duration of return to work after maternity leave was 4 weeks after maternity leave (0 - 6.8) for women with SLE and 2 weeks later (0 - 4) for controls (Mann-Whitney U test; p=0.977). No difference in number of women with delay of return to work after maternity leave (yes/no) was found between women with SLE and controls (n=9 versus n=11, respectively; OR=1.0, 95% CI [0.3-3.7], p=0.973). Conclusion: Pregnant women with SLE more frequently completely stop working or reduce working hours compared to matched healthy controls. These findings warrant improved counseling of these women and attention of health care providers, including company doctors. Disclosure of Interests: Birgit Blomjous Speakers bureau: UCB Pharma BV, Marieke ter Wee Grant/research support from: Nonrestricted grant from Lilly Netherlands BV, Speakers bureau: ARC Preceptorship program, Alexandre Voskuyl: None declared, Hanneke de Vries Grant/research support from: Pfizer, Speakers bureau: UCB Pharma BV, Irene E.M. Bultink Consultant for: Consultant fee from Sanofi Genzyme, Speakers bureau: Speaker fees from Lilly Netherlands BV, MSD Corp, Amgen BV, UCB Pharma BV, Roche Netherlands BV and Sanofi Genzyme